2014
DOI: 10.1016/j.celrep.2014.04.003
|View full text |Cite|
|
Sign up to set email alerts
|

Growth of the Developing Cerebral Cortex Is Controlled by MicroRNA-7 through the p53 Pathway

Abstract: Summary Proper growth of the mammalian cerebral cortex is crucial for normal brain functions and is controlled by precise gene expression regulation. We here have identified miRNA miR-7 that is highly expressed in cortical neural progenitors, and generated miR-7 sponge transgenic mice in which miR-7 silencing activity is specifically knocked down in the embryonic cortex. Blocking miR-7 function causes microcephaly-like brain defects due to reduced intermediate progenitor (IP) production and apoptosis. Upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 46 publications
(52 reference statements)
3
54
0
3
Order By: Relevance
“…Previous studies in rodent models found that P53-induced apoptosis is responsible for neuronal loss in many different congenital microcephalies. 32, 51, 52, 53, 54, 55 In some of these cases, P53 activation was correlated with increased DNA damage accumulation. 32, 52, 54, 55 The recent report that DNA damage and consequent P53 activation can result from increased mitosis length in neural progenitors 32 suggests that this mechanism could be much more common in microcephaly than previously thought, because many microcephaly genes have the potential to impact on mitosis timing.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in rodent models found that P53-induced apoptosis is responsible for neuronal loss in many different congenital microcephalies. 32, 51, 52, 53, 54, 55 In some of these cases, P53 activation was correlated with increased DNA damage accumulation. 32, 52, 54, 55 The recent report that DNA damage and consequent P53 activation can result from increased mitosis length in neural progenitors 32 suggests that this mechanism could be much more common in microcephaly than previously thought, because many microcephaly genes have the potential to impact on mitosis timing.…”
Section: Discussionmentioning
confidence: 97%
“…MicroRNAs (miRNAs) have emerged as important regulators of NPC proliferation and neocortex size [66][67][68][69][70][71][72].…”
Section: Micrornasmentioning
confidence: 99%
“…For example, circRNA Cdr1as is expressed exclusively in the brain and has more than 70 binding sites for miR-7, 59,60 which in turn regulates many other genes in the brain. 61–63 CDR1as may act like a sponge for miR-7, 59,60 and animals with a genetic disruption of Cdr1as had deficits in neurotransmission. 64 …”
Section: Rna Modificationsmentioning
confidence: 99%